Local synergistic collaboration between metallic Bi clusters, oxygen vacancies, and Cu atom enhances the electrochemical CO2-to-CH4 performance of CuO nanocatalysts - Yu-Chiao Tseng; Shih-Hsuan Chen; Kuang-Yi Liu; Yen-Lin Lai; Shu-Yu Lee; Chia-Shing Wu; Kuan-Wen Wang; Tsan-Yao Chen (Chemical Engineering Journal, 2025)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Applying expanded metal mesh for outdoor shades in outdoor thermal environments - Shing-Ru Yang; Shih-Tang Lan; Yi-Ting Wu; Tsuyoshi Honjo; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Applying Artificial Intelligence (AI) Techniques to Implement a Practical Smart Cage Aquaculture Management System - Chung-Cheng Chang; Jung-Hua Wang; Jenq-Lang Wu; Yi-Zeng Hsieh; Tzong-Dar Wu; Shyi-Chy Cheng; Chin-Chun Chang; Jih-Gau Juang; Chyng-Hwa Liou; Te-Hua Hsu; Yii-Shing Huang; Cheng-Ting Huang; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose This paper presents our team’s results to establish an AIoT smart cage culture management system. Methods According to the built system, the farmed field information is transmitted to the data platform of Ocean Cloud, and all collected data and analysis results can be applied to the cage culture field after the bigdata analysis. Results This management system successfully integrates AI and IoT technologies and is applied in cage culture. Using underwater biological analysis images and AI feeding as examples, this paper explains how the system integrates AI and IoT into a feasible framework that can constantly acquire information about the health status of fish, survival rate of fish, as well as the feed residuals. Conclusion The results of our research enable the aquaculture operators or owners to efficiently reduce the feed residual, monitor the growth of fish, and increase fish survival rate, thereby increasing the feed conversion rate.

Oxidative stress-induced apoptotic insults to rat osteoblasts are attenuated by nitric oxide pretreatment via GATA-5-involved regulation of Bcl-X L gene expression and protein translocation - Gong-Jhe Wu; Weu Wang; Yi-Ling Lin; Shing Hwa Liu; Ruei-Ming Chen (Archives of Toxicology, 2016)

Cell Hypertrophy and MEK/ERK Phosphorylation are Regulated by Glyceraldehyde-Derived AGEs in Cardiomyocyte H9c2 Cells - Shun-Yao Ko; I-Hsuan Lin; Tzong-Ming Shieh; Hsin-An Ko; Hong-I Chen; Tzong-Cherng Chi; Shu-Shing Chang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2013)

Characterization of a new phage, termed ϕA318, which is specific for Vibrio alginolyticus - Ying-Rong Lin; Chi-Wen Chiu; Feng-Yi Chang; Chan-Shing Lin (Archives of Virology, 2012)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Role of the DxxDxD motif in the assembly and stability of betanodavirus particles - Yi-Min Wu; Chi-Hsin Hsu; Chun-Hsiung Wang; Wangta Liu; Wei-hau Chang; Chan-Shing Lin (Archives of Virology, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Wogonin and fisetin induction of apoptosis through activation of caspase 3 cascade and alternative expression of p21 protein in hepatocellular carcinoma cells SK-HEP-1 - Yen-Chou Chen; Shing-Chuan Shen; Woan-Rouh Lee; Hui-Yi Lin; Ching-Huai Ko; Chun-Ming Shih; Ling-Ling Yang (Archives of Toxicology, 2002)

Neurotoxicity of mercury sulfide in the vestibular ocular reflex system of guinea pigs - Jiunn-Jye Chuu; Yi-Ho Young; Shing-Hwa Liu; Shoei-Yn Lin-Shiau (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)